1997
DOI: 10.1097/00005792-199711000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Fever of Unknown Origin (FUO): I. A prospective multicenter study of 167 patients with FUO, using fixed epidemiologic entry criteria

Abstract: Internal medicine wards in all 8 university hospitals in the Netherlands participated in this prospective study of fever of unknown origin (FUO) from January 1992 until January 1994 in order to update information on the spectrum of diseases causing FUO. We used fixed epidemiologic entry criteria to achieve completeness of enrollment and to avoid unintended selection bias. After entry, immunocompetent patients were included using criteria for FUO according to Petersdorf and Beeson (30). A standardized diagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
219
3
17

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(253 citation statements)
references
References 25 publications
14
219
3
17
Order By: Relevance
“…13 In the present study, the rate of diagnostic biopsy specimens compares favorably with that reported in previous publications, which was in the range of 14% to 20%. 9,14,15 We cautiously believe that we may attribute our modest increment in diagnostic yield of BMBX to a rate of 26% in our patient population to the fact that these patients had already undergone extensive work-up, including imaging studies. Performing CT and other imaging techniques as part of the early work-up of FUO can guide the treating physician to additional diagnostic procedures other than BMBX, 2,13 and as a consequence the patient population undergoing BMBX may differ from that in the past.…”
Section: Discussionmentioning
confidence: 96%
“…13 In the present study, the rate of diagnostic biopsy specimens compares favorably with that reported in previous publications, which was in the range of 14% to 20%. 9,14,15 We cautiously believe that we may attribute our modest increment in diagnostic yield of BMBX to a rate of 26% in our patient population to the fact that these patients had already undergone extensive work-up, including imaging studies. Performing CT and other imaging techniques as part of the early work-up of FUO can guide the treating physician to additional diagnostic procedures other than BMBX, 2,13 and as a consequence the patient population undergoing BMBX may differ from that in the past.…”
Section: Discussionmentioning
confidence: 96%
“…(6,8). Caseating granulomas are quite rare and have been described in only a few patients with CVID, and pose the additional challenge of thoroughly ruling out infectious etiology (11,13 (14)(15)(16)(17)(18). For instance, fever is a common accompaniment of hepatic granulomas and occurs in as many as 75% of cases (16,17).…”
Section: T a B L E 1 P R E V A L E N C E O F Au T O I N Mu N E Di Smentioning
confidence: 99%
“…Once an infectious etiology has been excluded, oral prednisone generally results in a prompt defervescence and symptomatic improvement (16,18,19). Nevertheless, in most series of FUO in the literature, granulomatous diseases make up less than 5% of diagnostic categories, usually labeled as "collagen diseases" or "inflammatory disorders" (14). The (4).…”
Section: T a B L E 1 P R E V A L E N C E O F Au T O I N Mu N E Di Smentioning
confidence: 99%
“…Más de la mitad de los casos se encontraban en estadio IV. La mayoría de las FOD ocasionadas por neoplasias se deben a los linfomas malignos, sobre todo cuando se encuentran en estadio avanzado (1,5,(10)(11)(12).…”
Section: Discussionunclassified